Analisis Pendekatan Pembelajaran CTL (Contextual Teaching And Learning) Di SMPN 2 Teluk Jambe Timur, Karawang - Abdul Karim (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
The purpose of this study is to analyze the learning approach Contextual Teaching and Learning (CTL) In SMP Negeri 2 Teluk Jambe Timur. Produce material to analyze the extent to which the pursuit approach has been run in school. To describe CTL learning approach include a) Design of Learning Activities; B) Implementation or Process of Learning Activities; C) Evaluation of learning outcomes. The research method used is descriptive research. In this research, the technique used to collect data is survey technique. The study population is all teachers of SMP Negeri 2 Teluk Jambe Timur that is 31 teachers. Data collection techniques used through the dissemination of questionnaires that have been tested for validity and reliability. The results showed that; The implementation of a contextual learner approach in SMP Negeri 2 Teluk Jambe Timur has been implemented at 71 percent or has an average grade of 2.85. Also, 29 percent or 1.15 is influenced by other learning approaches. In the first indicator, modeling has an average value of 2.59 or 64.75 percent has been implemented by teachers at school. In the second question indicator (Questioning) has an average grade of 3.02 or 75.5 percent has been implemented by teachers in school. In the third indicator, the Learning community has an average grade of 3.17 or 79.25 percent has been implemented by school teachers. In the fourth indicator, the inquiry (find) has an average value of 2.55 or 63.75 percent has been implemented by teachers in the school. In the fifth indicator of Constructivism has an average value of 3.19 or 79.25 percent has been implemented by teachers in school. On the sixth indicator, Reflection has an average grade of 3.44 or 86 percent has been implemented by school teachers. On the seventh indicator, Authentic Assessment has an average grade of 2.68 or 67 percent been implemented by school teachers.